PREVALENCE AND RISK FACTORS FOR CARDIOVASCULAR INVOLVEMENT IN PATIENTS WITH EARLY SYSTEMIC SCLEROSIS - Amikishiyev, S.; Okyar, B.; Ersoezlue, D.; Ozgur, D. S.; Bes, C.; Cefle, A.; Inanc, M. (Elsevier, 2025)
[Abstract Not Available]
Keywords: Descriptive Studies; Observational studies/registy